Anti-chondrosarcoma effects of PEDF mediated via molecules important to apoptosis, cell cycling, adhesion and invasion - Tan, M.; Choong, P.; Dass, Crispin (Academic Press, 2010)
Chondrosarcoma develops as a result of overgrowth of chondrocytes and overproduction of cartilage matrix. It is currently surgically treated, although non-invasive methods are being sought. In this report, pigment epithelium-derived factor (PEDF) induced apoptosis in the chondrosarcoma cell line - JJ012, with upregulation of Bax, Fas, caspase-3 and -6 and downregulation of Bcl-2. Cell cycling was also decreased with decreased expression of p38, p-Akt, p-Erk and JNK1 and increased expression of p73 and E2F1. Furthermore, PEDF increased adhesion of cells to collagen-I, with decreased expression of p-Fak, RhoA and cdc42. Invasion of cells through collagen-I was also reduced by PEDF, with decreased expression of uPAR, MMP-14 and increased expression of PAI-1. These findings seminally indicate that PEDF may have potential as an anti-cancer agent against chondrosarcoma.